Expression of basic fibroblast growth factor protein and its down-regulation by interferons in head and neck cancer - Riedel, Frank; Götte, Karl; Bergler, Wolfgang; Rojas, Walter Enrique; Hörmann, Karl (Head & neck, 2000)
Background Angiogenesis is crucial for tumor growth and metastasis. In several tumors, microvascular density has been shown to correlate with metastasis and aggressiveness. Basic fibroblast growth factor (bFGF) has potent angiogenic activity and has been identified in a wide variety of malignancies including head and neck squamous cell carcinomas (HNSCC). Material and Methods Frozen sections of 50 HNSCC were immunostained for von Willebrand factor and bFGF. Microvessels were counted by light microscopy; bFGF expression was studied at the light and electron microscopic level. Laryngeal cancer cell line HlaC79 was incubated with interferon (IFN) α and β. bFGF quantification was performed by ELISA, and antiproliferative effects were determined by BrdU assay. Results The mean number of blood vessels (77.5 ± 23.7) is significantly increased in HNSCC compared with controls (17.1 ± 5.9). bFGF protein expression was detected in all HNSCC but not in control tissue. An correlation between bFGF expression and mean number of microvessels was found (p < .001). However, no correlation between bFGF expression and the main clinicopathologic features was shown. The long-term exposure (144 hr) of HNSCC cells to noncytostatic concentrations of IFN α and β (>10 U/mL) down-regulated the protein production of bFGF. Conclusion bFGF expression and angiogenesis are enhanced in HNSCC. The higher microvessel density in HNSCC with strong bFGF expression supports the importance of bFGF for tumor angiogenesis. IFN α and β treatment leads to a down-regulation of bFGF expression independent of their antiproliferative effects, suggesting that IFN treatment might result in a reduction of angiogenesis in HNSCC. © 2000 John Wiley & Sons, Inc. Head Neck 22: 183-189, 2000.